Co-occurrence of biphenotypic acute leukaemia, glucose 6-phosphate dehydrogenase deficiency and haemoglobin E trait in a single child - Mallick, Debkrishna (BMJ Case Rep, 2016)
Acute leukaemias occur as the result of clonal expansion subsequent to transformation and arrest at a normal differentiation stage of haematopoietic precursors, which commit to a single lineage, such as myeloid or B-lymphoid or T-lymphoid cells. Biphenotypic acute leukaemia (BAL) constitutes a biologically different group of leukaemia arising from a precursor stem cell and co-expressing more than one lineage specific marker. The present report describes a child with unusual co-occurrence of biphenotypic (B-precursor cell and Myeloid) acute leukaemia, haemoglobin E trait and glucose 6-phosphate dehydrogenase (G6-PD) deficiency. To the best of our knowledge, this constellation of haematological conditions in a single child has never been described before.